Electronics of Modern Children World of Culture - Davlatova Zebo Haydarovna (Research Parks Publishing LLC, 2022)
This article will focus on the positive and negative impact of digital technologies on children, the search for solutions to negative aspects, digital devices that can be used in preschool education, and their introduction into the education system.